Clinical Reasoning: A Case of Acute Akinetic Mutism and Encephalopathy. (25th October 2022) - Jain, Varun; Remley, William; Bunag, Cyra; Rodriguez, Elsa; Albayram, Mehmet S.; Wilson, Christina; Patterson, Addie; Bonnell, Gabriel; Okun, Michael S.; Patel, Bhavana
Abstract : A 70-year-old, right-handed African American man presented with 5 days of severe abdominal and diffuse body pain. He has a history of hemoglobin SC (Hb SC) disease, rheumatoid arthritis (RA), and a provoked pulmonary embolism (PE) 1 year before the current presentation. He was not on anticoagulation or any psychotropic medications but recently had completed a short steroid course for joint pain. Initial evaluations included a complete blood count, comprehensive metabolic panel, lipase, urine culture, blood cultures, urine toxicology, and CT scan of the abdomen and pelvis (with and without contrast). The diagnostic evaluations were unremarkable, except for a leukocytosis of 22, 000/mm 3 believed to be steroid-induced. He was subsequently treated for a vaso-occlusive pain crisis with intravenous fluids and opioids. On day 3 of hospitalization, he was nonverbal and unable to follow commands and move his extremities. Examination revealed normal vital signs. He was awake with spontaneous eye opening with intermittent tracking; pupils were symmetric, round, and reactive; oculocephalic reflex was intact; and no facial asymmetry was present. Signs of meningeal irritation were absent. He had no vocalizations, did not follow commands, had sparse spontaneous antigravity movements in all extremities, and no response to noxious stimuli. He had hyperreflexia in upper and lower extremities with normal tone. No involuntary movements were observed. Neuroimaging included CT angiography of the head and neck and MRI of the brain (without contrast) inclusive of gradient echo sequences (GREs), which did not reveal an acute intracranial process. MRI of the brain without contrast with susceptibility-weighted imaging (SWI) performed a week later showed supratentorial multifocal microhemorrhages (Figure). CSF revealed 0 white blood cells (WBCs), 1 red blood cell (RBC), an elevated protein of 178 mg/dL, and xanthochromia. EEG revealed no epileptiform discharges. Given his unexplained neurologic decline, he was transferred to our hospital.